Perilla– a lesser known food crop - Kumar Soni, Jeetendra; Lungmuana,; Amit Kumar,; Shakuntala, I (Indian Farming, 2022)
Mizoram is blessed with rich Perilla biodiversity. Thus, exploration, collection and conservation of germplasm, and further selection of best-performing genotypes is important for improving yield and quality. More research is required for promising germplasm with scientific knowledge and breeding techniques to escalate the productivity and potential of Perilla cultivation. Also, utilization of available genetic resources will ensure high productivity and ability to develop varieties.